Attitude of Parents Referred to the Department of Pediatric Dentistry towards Different Behavioral Management Techniques Used in Pediatric Dentistry - Jafarzadeh, Mahdi; Kooshki, Fahimeh; Malekafzali, Beheshteh; Ahmadi, Soudabeh (Journal of Dental School, 2019)
Objective: Behavior management of uncooperative children is an important principle in pediatric dentistry. By adopting an appropriate behavior management technique, pediatric dentists can treat patients more effectively and create a positive attitude towards dentistry in them. This study aimed to assess the attitude of parents presenting to the Department of Pediatric Dentistry at Isfahan University, School of Dentistry towards different behavior management techniques used for uncooperative children. Methods: This cross-sectional study was conducted in the Department of Pediatric Dentistry at Isfahan University, School of Dentistry. Fifty-four parents watched a film regarding seven popular behavior management techniques namely tell-show-do, voice control, use of passive restraint devices, active restraint (physical restraint by dental personnel or the parents), use of oral sedatives, hand over mouth and general anesthesia. After watching each technique, the parents expressed their opinion regarding the level of acceptability of the respective technique using visual analog scale (VAS). Data were analyzed using the Tukey’s HSD test, repeated measures ANOVA, paired t-test and the Student’s t-test. Results: Of 54 parents, 36 were females and 18 were males aged 23 to 68 years. Of the mentioned techniques, the tell-show-do technique had the highest acceptability (94%). Hand over mouth and use of passive restraint devices had the lowest acceptance (30% and 35%, respectively). Except for the mentioned two, the remaining techniques were well accepted by the parents (52%). No significant association was found between any of the behavior management techniques and age, level of education or occupation of parents. Conclusion: It appears that acceptability of the behavior management techniques has significantly changed over time and advanced pharmaceutical management techniques have gained increasing acceptance.